(untitled) (Tempo e Argumento, 2024)
This article seeks to contribute to the ongoing debate concerning the role of the entrepreneurial community during the political transition in Brazil, specifically on the government of Ernesto Geisel (1974-1979). The central analytical perspective of this study posits that representatives of the private enterprise, regardless of the origin of their capital, actively safeguarded their business interests by engaging in political activities to ensure stability in countries influenced by capital and to maintain their dominant social class. To achieve this objective, the research relies on both theoretical and empirical analyses of the relationship between entrepreneurship and dictatorship, drawing from the historiographical discourse on the subject and recognizing these studies as an established historiographical perspective in recent years. Building upon the foundations laid by this historical perspective, the article proceeds to delve into the configuration of the regime established in 1964, aptly described as an entrepreneurial-military regime. This interpretation is presented in two distinct sections. The first section addresses the theoretical dimension by exploring the outcomes of the period following the 1964 entrepreneurial-military coup and its connection with the capitalist system and the United States. In the pursuit of an empirical approach, the research draws upon primary source documents, particularly those sourced from the personal archives of Ernesto Geisel and Antônio Azeredo da Silveira. These archival materials provide concrete examples that lend support to the interpretations presented in the article. Employing a methodology of qualitative content analysis, the documentation data is scrutinized and interpreted to derive meaningful insights. This article contributes to an understanding of the interplay between the entrepreneurial community and the Brazilian political landscape during the transition.